دراسة أثر الاستشفاء في شعبة الحواضن على خيار الرضاعة الوالدية ومدتها - شريتح أحمد; عثمان منير; خضور لينا (Latakia University Journal -Medical Sciences Series, 2019)
حليب الأم هو الغذاء الأنسب للرضيع خلال الأشهر الستة الأولى من الحياة فهو كمركب بيولوجي يُسهم بشكل كبير في خفض نسبة الوفيات الناجمة عن الأمراض الإنتانية وأخطاء التغذية، خاصة في الدول الفقيرة. محلياً كان لابد من إجراء دراسة مستقبلية(15/3/2005 لغاية 15/3/2006) تبين الأثر السلبي المحتمل لاستشفاءالولدان في شعبة الحواضن في مشفى الأسد الجامعي على خيار الإرضاع الوالدي ومدتها بملء استبيان يتضمن أسئلة متعلقة بالأم والحمل والجنين ومشاكله الصحية ثم متابعة الأمهات هاتفيا مدة 6اشهرلمعرفة نسبة الاستمرار بالرضاعة الوالدية. تم تحليل النتائج بعد سنة من الدراسة وكانت كالآتي: تم ملء استبيان من قبل 134 امرأة وأمكن استثمار 118 منها بنسبة88% كانت نسبة الإرضاع الصناعي بشكل مطلق 35% ونسبة الإرضاع الوالدي 65% لاحظنا وجود علاقة إيجابية مؤكدة لفشل الإرضاع الوالدي بعد الاستشفاء مع تدني عمر الأم ومستوى تعليمها والولادة القيصرية ومدة إقامة الوليد في شعبة الحواضن رغم وجود دعم وتشجيع عائلي كبيرين، بينما لم يكن لجنس المولود وتعدد الحمول وعمل الأم دور في ذلك. ورغم الصعوبات يجب أن نؤكد على وجود كادر طبي تمريضي خبير يسهم في توعية الأم ويهيئ أحسن السبل والوسائل لمتابعة الرضاعة الوالدية ويقلل نسبة الفشل فيها. Mother milk is the most suitable food for the newborn in the first six months of his life. As a biological composition, it contributes to decreasing death ratios caused by infectious diseases and wrong feeding especially in poor countries. Locally, there was a great need for making future study (15/03/2005 — 15/03/2006) to show the probable negative effect of newborns therapy at the nursing Department in Al-Assad University Hospital on the choice of natural sucking and its duration through filling a questionnaire including questions related to mother, pregnancy, fetus and its health problems. Mothers were then followed up through telephone for six months to know the percentage of mothers who continued sucking. After one year, the result was as follows: 134 women filled the questionnaires, 118 of them were used a percentage of 88%. The percentage of women who used artificial sucking was 35%; and the percentage of those who used natural sucking was 65%. A positive relation was found between the failure of natural sucking after therapy and the decrease in mother’s age, her educational level, cesarean birth and the duration of staying at the department of nurses despite of great encouragement by families, whereas the newborns’ genders and the number of previous pregnancies were of no effect. Despite all difficulties, it is highly recommended to have experienced nursing medical staff to contribute to cautioning mothers and to prepare the best ways and means to keep using natural sucking in order to decrease ratios of failure.